ANALISIS PESAN DAN SALURAN KOMUNIKASI TOKOH ADAT DALAM MELESTARIKAN KEARIFAN LOKAL APPARAMMULA MASYARAKAT TRANSMIGRAN MAKASSAR DESA TUMBUDADIO KECAMATAN TIRAWUTA KABUPATEN KOLAKA TIMUR - Sunusi, Riska; Dilla, Sumadi; Jaya, Asrul (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2019)
ABSTRACT The purpose of this study was to identify and describe the messages and communication channels of traditional leaders in preserving the local wisdom of the Makassar transmigrant community Tumbudadio Village Tirawuta District, East Kolaka District. The subject of this research is the entire community in Tumbudadio Village, Tirawuta Subdistrict, East Kolaka Regency with 5 informants. The technique for determining informants in this study is purposive sampling technique. Data collection techniques used in this study are observation, interviews, literature study and documentation. While the data analysis technique used in this research is descriptive qualitative which describes, analyzes, describes the conclusions of the results of the research that are connected with relevan theories. The results showed that the messages and communication channels of traditional leaders in preserving the local wisdom of the Makassar transmigrant community Tammudadio Village Tirawuta District, East Kolaka District, consisted of communication messages related to traditional advice and environmental preservation where the form of the message was informative and persuasive which was realized in the sipakatau, sipakainge culture and kasipalli. while the communication channel used consists of deliberation, traditional rituals, non-formal discussions, two-way communication such as meetings between traditional leaders and the local community as well as the activities of assurommaca pare beru (new rice thanksgiving). With the existence of messages and communication channels carried out by traditional leaders and the community is able to maintain the existence of the apparammula tradition in the Tumbudadio village community Tirawuta District, East Kolaka Regency. Keywords: Communication Messages; Communication Channels; Local Wisdom of Apparammula.